Analisis Proses Pembelajaran Bahasa Arab Siswa Kelas VIII Madrasah Tsanawiyah Nurul Hidayah Way Kanan - Ita Nurmala; Masfiyatul Asriyah; M. Ari wibowo (Al Mitsali : Jurnal Penelitian dan Pendidikan Bahasa Arab, 2022)
The purpose of this research is to analyze the process of learning Arabic at MTs Nurul Hidayah, looking for problems that impede learning, and knowing the solutions made by the teacher to overcome the problems that arise in the learning process. The questions in this study include "How is the implementation of learning Arabic in terms of learning methods and media in class VIII MTs Nurul Hidayah?". This research is a qualitative descriptive study. The subjects in this study were Arabic subject teachers, class VIII students of MTs Nurul Hidayah, Way Kanan, and other school officials. Based on the research that has been done, the results of this study indicate that: 1) the implementation of learning Arabic in class VIII MTs Nurul Hidayah can generally be said to be good, and meets the requirements for implementing learning. The learning method used is the direct method, the lecture method and the translation method, 2) the learning problems found in class VIII MTs Nurul Hidayah are the lack of student interest in learning Arabic, low student learning motivation, learning media factors, social environmental factors, teacher factors , infrastructure factors, and little learning time, and 3) the solution made by the teacher is to provide more frequent motivation to students, trying to present appropriate learning media, getting used to speaking Arabic starting from the classroom environment, maximizing class hours, sticking mufradat in every object in the school, present teachers who are in accordance with their fields, require teachers to make lesson plans, and complete facilities and infrastructure that are not yet available.